Formative Assessment and Professional Training: Reflections from a Mathematics course in Bioengineering - Carrere, C. (2016)
Bioengineering is currently considered an interdisciplinary professional field which provides solutions to different problems arising in the area of health care. Its strategic importance is widely acknowledged since its developments and proposals could help diminish the level of technological dependence in the sector. The fast pace of innovation in the area of biomedical technology gives rise to permanent reflection on the learning goals and teaching strategies proposed by educators in the different training stages of a bioengineer. In this context, learning assessment appears as a controversial issue which needs to be debated and rethought. This paper describes the reflections of teachers of a Mathematics course within a Bioengineering program around the question, What approach to assessment favors the student's participation, autonomy and training as a future bioengineer? The investigation was carried out in the framework of a Participatory Research Action project and helped us to redesign assessment activities from a different perspective.